Framing Agricultural Media: An Analysis of Critical Discourse of Business CNN and CNN Indonesia using van Dijk's Theory - Andini; Rohmah Sinta Nuriyah; Janefa Astrid Endang Rahmadian (Pawarta: Journal of Communication and Da'wah, 2025)
This study analyzes the representation of foreign workers in the United States agricultural industry using the critical discourse analysis (CDA) model by Teun A. Dijk. Using a case study from a CNN Business article titled "America's Farmers Are in Desperate Need of Workers. Foreigners are the answer" (2016), this study explores how mass media shapes public opinion on employment and immigration issues. The Dijk model, which includes the structural dimensions of the text (macrostructure, superstructure, microstructure), social cognition, and social context, is used to uncover the symbolic discourse and ideological construction of the media. The analysis revealed that CNN Business systematically framed the labor shortage problem as an urgent national crisis, positioning foreign workers as the "saviors" of agricultural productivity by using positive diction and problem-solving narratives. The study also compared it to CNN Indonesia's article on the potential abuse of social assistance in regional elections, highlighting how the media shapes social realities and directs public opinion according to their respective ideological contexts. This study concludes that the mass media play an active role in shaping and directing public opinion through linguistic strategies and hidden rhetoric embedded in news texts. Therefore, critical media literacy is essential for the public to understand biased narratives and potential hidden agendas in media coverage.